Human Resource Information System sebagai Alat Strategis dalam Penguatan Fungsi HR Management: Studi Efektivitas dan Efisiensi - Yamin, Muhammad (Journal of Current Research in Management, Policy, and Social Studies, 2025)
Digital transformation in bureaucracy requires the public sector to manage human resources (HR) more effectively, efficiently, and accountably. One of the key instruments supporting this effort is the Human Resource Information System (HRIS), which is part of electronic Human Resource Management (e-HRM). HRIS functions to automate administrative processes, integrate personnel data, and provide relevant information for strategic decision-making. This study employs a literature review approach to analyze the contribution of HRIS in enhancing the efficiency and effectiveness of HR management, by examining both national and international publications. The findings show that HRIS plays an important role in reducing administrative burdens, improving data accuracy, strengthening transparency, and supporting more objective performance appraisal. Furthermore, HRIS facilitates employee competency development, the application of a merit system, and evidence-based talent planning. However, the implementation of HRIS in the public sector faces challenges such as inconsistent data quality, limited digital literacy among employees, resistance to change, and issues of data integration and security. To optimize HRIS as a strategic function, good data governance, user competency development, cross-government system integration, and continuous evaluation are required. With these strategies, HRIS has the potential to serve as a strategic enabler for a modern bureaucracy that is professional, transparent, accountable, and oriented toward improving the quality of public services.